2020
DOI: 10.15560/16.3.535
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sea holothurians (Echinodermata, Holothuroidea) from the Colombian Southern Caribbean Sea

Abstract: Fifteen morphotypes of deep-sea holothurians were documented by photography or videography at depths of 596–2,566 m, using Remote Operated Vehicles (ROV) video surveys and towed camera transects, during hydrocarbon exploratory activities in the Colombian Southern Caribbean. Most of the morphotypes were identified to the species level based on the images. The species belong to four orders, Apodida (1 species), Persiculida (3 species), Elasipodida (8 species), and Synallactida (3 species). Four species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Diversity information of deep-sea echinoderm fauna through recent research is scarce (Pawson, 1982;Stöhr and Segonzac, 2005;Mecho et al, 2014;Moles et al, 2015;Calero et al, 2017;Mironov et al, 2018;Setyastuti and Wirawati, 2018;Stöhr and O'Hara, 2021). Strong progress has been made, especially for Colombia, Chile, Brazil, Argentina and Mexico (González et al, 2002;Borrero-Pérez et al, 2003;Benavides-Serrato and Borrero-Pérez, 2010;Campos et al, 2010;Manso, 2010;Massin and Hendrickx, 2011;Borrero-Pérez et al, 2012;Hendrickx et al, 2014;Solís-Marín et al, 2014;Martínez et al, 2014;Martínez et al, 2015;Martínez, 2016;Conejeros-Vargas et al, 2017;Martinez and Penchaszadeh, 2017;Martínez et al, 2017, Rivadeneira et al, 2017Luna-Cruz and Hendrickx, 2018;Borrero-Pérez et al, 2019;Flores et al, 2019;Pertossi et al, 2019;Martínez et al, 2019;Borrero-Pérez et al, 2020;Martinez et al, 2020;Rivadeneira et al, 2020;Luna-Cruz and Hendrickx, 2020;Catalán et al, 2020;Luna-Cruz and Hendrickx, 2021;Flores et al, 2021).…”
Section: Regional Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity information of deep-sea echinoderm fauna through recent research is scarce (Pawson, 1982;Stöhr and Segonzac, 2005;Mecho et al, 2014;Moles et al, 2015;Calero et al, 2017;Mironov et al, 2018;Setyastuti and Wirawati, 2018;Stöhr and O'Hara, 2021). Strong progress has been made, especially for Colombia, Chile, Brazil, Argentina and Mexico (González et al, 2002;Borrero-Pérez et al, 2003;Benavides-Serrato and Borrero-Pérez, 2010;Campos et al, 2010;Manso, 2010;Massin and Hendrickx, 2011;Borrero-Pérez et al, 2012;Hendrickx et al, 2014;Solís-Marín et al, 2014;Martínez et al, 2014;Martínez et al, 2015;Martínez, 2016;Conejeros-Vargas et al, 2017;Martinez and Penchaszadeh, 2017;Martínez et al, 2017, Rivadeneira et al, 2017Luna-Cruz and Hendrickx, 2018;Borrero-Pérez et al, 2019;Flores et al, 2019;Pertossi et al, 2019;Martínez et al, 2019;Borrero-Pérez et al, 2020;Martinez et al, 2020;Rivadeneira et al, 2020;Luna-Cruz and Hendrickx, 2020;Catalán et al, 2020;Luna-Cruz and Hendrickx, 2021;Flores et al, 2021).…”
Section: Regional Comparisonmentioning
confidence: 99%
“…2003;Benavides-Serrato and Borrero-Pérez, 2010;Borrero- Pérez et al, 2012;Borrero-Pérez et al, 2019;Dueñas et al, 2021). For the Southern Colombian Caribbean region, 16 species of sea cucumbers are found between 596 and 2566 m(Borrero- Pérez et al, 2020), of which only four have been reported for the Costa Rican Caribbean (B. sanguinolenta, Benthothuria funebris, Deima validum validum, and Paroriza pallens).…”
mentioning
confidence: 99%
“…The phylum Echinodermata has approximately 7,510 species (WoRMS, 2022) divided into five classes: Crinoidea (lilies or sea feathers, 673 species); Asteroidea (starfish, 1,923 species); Ophiuroidea (brittle stars, 2,126 species); Echinoidea (sea urchins, 1,015 species), and Holothuroidea (sea cucumbers, 1,773 species) (Pawson, 2007;Pawson et al, 2009;WoRMS, 2022), all of which have been recorded for the Colombian Caribbean whose current inventory includes 298 species (Benavides-Serrato et al, 2011;Borrero-Pérez et al, 2012;López-Sánchez et al, 2013;Borrero-Pérez et al, 2019;Borrero et al, 2020). However, these studies do not include localities in the shallow coastal zone of the Department of Atlántico.…”
Section: Introductionmentioning
confidence: 99%
“…Latest publications on deep-sea megafauna in the Colombian Southern Caribbean have laid out several species imagery records setting these images as basis for new species diversity exploration and ecological information (Acero et al, 2018;Victorero et al, 2018;Borrero-Pérez, Dueñas, León, & Puentes, 2020), but mostly performing Remotely Operated Vehicle (ROV) video surveys and towed camera transects, only. However, a vast majority of the ecosystems in bathyal, abyssal, and hadal zones are still unexplored, while the pressure to license areas of the deep ocean are only intensifying (Borrero-Pérez, Dueñas, León, & Puentes, 2020). On the other hand, several explorations and new data on Latin American countries' deep-sea territories have come out from oil and gas companies (Borrero-Pérez et al, 2020;Dueñas et al, 2019;Grijalba-Bendeck et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, a vast majority of the ecosystems in bathyal, abyssal, and hadal zones are still unexplored, while the pressure to license areas of the deep ocean are only intensifying (Borrero-Pérez, Dueñas, León, & Puentes, 2020). On the other hand, several explorations and new data on Latin American countries' deep-sea territories have come out from oil and gas companies (Borrero-Pérez et al, 2020;Dueñas et al, 2019;Grijalba-Bendeck et al, 2019). These companies also fund programs and consortiums at universities to conduct basic research, which could apply to the industry in the future.…”
Section: Introductionmentioning
confidence: 99%